The French cartographer and the clan chief: archaeological fieldwork in Perthshire, 1763 - Keppie, Lawrence (Proceedings of the Society of Antiquaries of Scotland, 2016)
In June 1763 a Frenchman, identifiable as the cartographer Louis Stanislas De la Rochette, journeyed from Edinburgh into Perthshire in the company of Sir James Macdonald, eighth baronet of Sleat in Skye. Visits were made to the Roman sites at Ardoch, Kaims Castle, Strageath and Dalginross. Bound up with De la Rochette’s manuscript accounts of his journey to and sojourn in Scotland are a finished drawing of Ardoch and three of the fort and temporary camp at Dalginross, the latter valuably annotated with measurements, including those of the camp’s ‘Stracathro-type’ gates. The drawings can be compared with those made only a few years earlier by William Roy. De la Rochette, who had come to Scotland in 1763 ostensibly to see to the repatriation of French prisoners of war, became a well-known mapmaker in late 18th-century London.